2014
DOI: 10.1371/journal.pone.0109582
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Prophylactic Dexamethasone on Nausea and Vomiting after Thyroidectomy: A Systematic Review and Meta-Analysis

Abstract: BackgroundWe carried out a systematic review and meta-analysis to evaluate the impact of prophylactic dexamethasone on post-operative nausea and vomiting (PONV), post-operative pain, and complications in patients undergoing thyroidectomy.MethodsWe searched Pubmed, Embase, and Cochrane Library databases for randomized controlled trials (RCTs) that evaluated the prophylactic effect of dexamethasone versus placebo with or without other antiemetics for PONV in patients undergoing thyroidectomy. Meta-analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…This finding may be logical, considering our finding that the reduction in fentanyl consumption was correlated with postoperative nausea scores. In addition, although the mechanism of postoperative nausea after thyroidectomy is not clear, intense vagal stimulation during surgical manipulation of the neck may contribute [7,8]. Lidocaine may suppress the The reduction in pain after thyroidectomy, together with reduced postoperative nausea, suggests that intravenous lidocaine improves the quality of recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding may be logical, considering our finding that the reduction in fentanyl consumption was correlated with postoperative nausea scores. In addition, although the mechanism of postoperative nausea after thyroidectomy is not clear, intense vagal stimulation during surgical manipulation of the neck may contribute [7,8]. Lidocaine may suppress the The reduction in pain after thyroidectomy, together with reduced postoperative nausea, suggests that intravenous lidocaine improves the quality of recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative nausea and vomiting (PONV) also occurs following thyroid surgery [5][6][7]. Although the mechanisms of PONV after thyroidectomy are not clear, stimulation of vagal afferents and inflammatory responses resulting from surgical injury of the neck structure may be responsible [7,8]. Lidocaine may effectively control both pain and PONV after thyroidectomy.…”
Section: Introductionmentioning
confidence: 99%
“…17 A meta-analysis of patients undergoing thyroidectomy found that dexamethasone at 8-10 mg had the greatest effect in reducing PONV. 18 The DREAMS trial examined whether preoperative dexamethasone reduces postoperative vomiting in patients undergoing elective gastrointestinal surgery. Reduction of PONV in this group of patients could improve the surgical experience and also fast track recovery and decrease postoperative complications.…”
Section: What This Study Addsmentioning
confidence: 99%
“…It has been shown that dexamethasone effectively reduced PONV and postoperative pain in patients undergoing thyroidectomy [18,19,21,22]. In addition, higher dexamethasone doses (8-10 mg) are generally more effective than lower dexamethasone doses (1.25-5 mg) [22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, higher dexamethasone doses (8-10 mg) are generally more effective than lower dexamethasone doses (1.25-5 mg) [22]. The timing of dexamethasone administration is also an important factor.…”
Section: Discussionmentioning
confidence: 99%